GAMBARAN PROFIL DARAH ITIK PEKING (ANAS PLATYRHYNCHOS) SETELAH DIBERIKAN EKSTRAK AKUADES DAUN KEDONDONG PAGAR (LANNEA COROMANDELICA) - Safrida Safrida; Asiah Asiah; Syukriah Syukriah (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2016)
ABSTRACTThis study was designed to determine the effect aqueous extract of Lannea coromandelica leaf at concentrations of erythrocytes and leukocytes in peking duck (Anas platyrhynchos). Experimental design used was Completely Randomized Design (CRD) consisted of 3 experimental treatments, each consisted of 8 ducks i.e., P0 (control), P1 (given aqueous extract of Lannea coromandelica leaf as much as 780 mg / mL / day / kg body weight), P2 (given aqueous extract of Lannea coromandelica leaf as much as 1560 mg / mL / day / kg body weight). Data were analyzed using analysis of variance (ANOVA). The results showed that the aqueous extract of Lannea coromandelica significant effect (p <0.01) in concentrations of erythrocytes peking duck, but had no effect (P>  0.01) in concentrations of the leukocytes. Average erythrocytes in all treatments, 2081667-2300000 per mm 3. The average number of leukocytes in all treatments, 23175-23500 per mm3. It was concluded that the aqueous extract of Lannea coromandelica leaf have effect on the increase concentrations of erythrocytes peking duck (Anas platyrhynchos).